2022
DOI: 10.21565/ozelegitimdergisi.874247
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Psychometric Characteristics of Mathematical Modeling Competencies Scale: Gifted and Talented Youth

Abstract: Introduction: It can be claimed that mathematical modeling, which is a key concept in terms of creating original projects with the developed models, is important in the education of gifted youth. Determining their modeling competencies and identifying the stages that they need to develop will provide essential data in terms of deciding on what kind of educational practices and program differentiation will be carried out. The study aims to develop a scale for mathematical modeling competencies and to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The internal consistency coefficients, Cronbach's alpha, were α = 0.958 for the whole scale and 0.811, 0.900, 0.883, 0.820, and 0.927 respectively for each sub-factor of IP, US, M, WM, and IV respectively. Fit indices (χ 2=df = 2.00, GFI = 0.90, RMSEA = 0.075, SRMR = 0.063, IFI = 0.97, NNFI = 0.97, CFI = 0.97, NFI = 0.94, PNFI = 0.86) demonstrated that the instrument has a valid structure ( Özbek & Köse, 2022). The Content Validity Index, which represents the mean value of the items' Content Validity Ratio, was found to be very high with 0.95 ( Özbek & Köse, 2022).…”
Section: Instrumentsmentioning
confidence: 95%
See 3 more Smart Citations
“…The internal consistency coefficients, Cronbach's alpha, were α = 0.958 for the whole scale and 0.811, 0.900, 0.883, 0.820, and 0.927 respectively for each sub-factor of IP, US, M, WM, and IV respectively. Fit indices (χ 2=df = 2.00, GFI = 0.90, RMSEA = 0.075, SRMR = 0.063, IFI = 0.97, NNFI = 0.97, CFI = 0.97, NFI = 0.94, PNFI = 0.86) demonstrated that the instrument has a valid structure ( Özbek & Köse, 2022). The Content Validity Index, which represents the mean value of the items' Content Validity Ratio, was found to be very high with 0.95 ( Özbek & Köse, 2022).…”
Section: Instrumentsmentioning
confidence: 95%
“…It simplifies and expresses real-life problems mathematically to solve, interpret, and validate the real-life problems through developing interdisciplinary models (Borromeo Ferri, 2006;Maaß, 2006;Tekin Dede, 2017). This study is grounded on the theoretical framework (Borromeo Ferri, 2006) of mathematical modelling cycle (see Figure 1) and competencies based on multi-steps of the modelling process ( Özbek & Köse, 2022). It starts project with the 'identifying the real-life problem', continues with the 'understanding and simplifying the problem', 'mathematizing', 'working mathematically' and culminates project with 'interpretation and validation'.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In the previous studies, it was found that gifted youth might be successful in project production by solving competitional global problems, and integrating into virtual environments (Çetinkaya, 2020). There have been studies on the examination of gifted youth views on the effectiveness of education program, their views were found to be positive, (Kayişdağ & Melekoğlu, 2019) and project productions on how they transformed their talents, skills, knowledge and competencies such as mathematical modelling (Özbek & Köse, 2022) and reflective thinking into creative production. Also, innovative approaches such as mathematical modelling-based PPMP and project-based activities were examined in terms of project qualifications of gifted youth and positive changes resulted in project production (Çetinkaya, 2020; Özbek & Cho, 2022).…”
Section: Introductionmentioning
confidence: 99%